Correlation between peer assessment score and final examination mark among IIUM first year Medical students - Ab Rahman, Jamalludin; Mohd Rus, Razman; Samsuddin, Niza (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Background: Peer assessment has been shown to complement both formative and summative evaluations in education and used in some medical programmes. The study was aimed to find correlation between group work peer assessment score and final examination mark among four batches of International Islamic University Malaysia (IIUM) first year MBBS students. Method: A set of four questions was constructed and tested to assess students’ overall role in their group research project. The difference in distribution according to years was tested by using one-way ANOVA or Kruskal-Wallis, depending on the data distribution. Pearson correlation coefficient test was done to test the linear association between peer score and final examination mark. Partial correlation test was used to adjust the correlation for four academic years. Results: From the analysed data of 502 students, there was moderate, significant positive correlation (0.366) between peer assessment score and the final examination mark (P < 0.001). Adjustment to the academic years resulted in correlation coefficient of 0.371. Conclusion: The results provide an important insight on the influence of peers’ perception in predicting the medical student academic performance.